Overview of multimorbidity research in India: a scoping review protocol [version 2; peer review: 2 approved] - Arpita Ghosh; Siaa Girotra; Parul Puri (Wellcome Open Research)
Background Due to demographic and epidemiological shifts, people are living until older ages with more morbidities. These morbidities often have shared pathophysiology, which leads to a rise in coexisting health issues known as 'multimorbidity'. Primary care studies and disease burden surveys have multiplied, unveiling varied aspects of multimorbidity, yet with inconsistent definitions and methods. This protocol aims to guide an in-depth and comprehensive exploration of multimorbidity research in India through a scoping review, to understand the extent, range, and nature of research on multimorbidity in India. Methods This study will comprehensively search the PubMed/Medline, Cochrane, and Embase databases employing a well-defined strategy. All studies published in English will be considered, provided the focus is multimorbidity and there is information specifically from India. Two reviewers will independently screen the search outcomes, and data extraction will include multimorbidity definitions, data and methods, patterns, risk factors and outcomes. The research will follow the Joanna Briggs Institute framework and adhere to PRISMA-P 2015 guidelines for reporting. Descriptive statistics and narrative synthesis will be used to summarize findings. Conclusions Findings from this review will shed light on the extent and nature of multimorbidity research in India and help guide future research.